Attribution of cause of end-stage renal disease among patients with systemic lupus erythematosus: the Georgia Lupus Registry. (22nd January 2016) - Plantinga, Laura C; Drenkard, Cristina; Pastan, Stephen O; Lim, S Sam
Abstract : Objective: Whether using provider-attributed end-stage renal disease (ESRD) cause of systemic lupus erythematosus (SLE) in national surveillance data captures the entire population of patients with SLE and ESRD remains uncertain. Our goal was to examine attributed cause of ESRD in US surveillance data among patients with SLE who have developed ESRD. Methods: Data from a national registry of treated ESRD (United States Renal Data System (USRDS)) were linked to the population-based Georgia Lupus Registry (GLR). The provider-attributed cause of ESRD was extracted from the USRDS for each validated patient with SLE in the GLR (diagnosed through 2004) who initiated treatment for ESRD through 2012. The percentage of these patients with SLE whose ESRD was subsequently attributed to SLE in the USRDS was calculated, overall and by patient characteristics. Results: Among 251 patients with SLE who progressed to ESRD, 78.9% had SLE as their attributed cause of ESRD. Of the remaining 53 patients, 43.4%, 18.9% and 15.6% had ESRD attributed to hypertension, diabetes mellitus type II and non-SLE-related glomerulonephritis, respectively. Attribution of ESRD to SLE was higher among patients aged ≤30 (87.9–93.9%) vs >30 (52.6%; p<0.001) but did not differ by sex or race. Having Medicaid (86.2%) or no insurance (93.5%) was associated with greater attribution of ESRD to SLE than having private insurance (72.5%; p=0.02), as was having two or more providers state a diagnosis of SLE (89.0% vs 73.5% with a rheumatologist diagnosis alone; p=0.008). Conclusions: These estimates indicate that USRDS-based studies may underreport ESRD among US patients with SLE. However, observed patterns of differential attribution of ESRD cause, particularly by age, suggest that providers may be correctly attributing ESRD to causes other than SLE among some patients with SLE.